Casting defects in structural components: Are they all dangerous? A 3D study. (December 2018) - Serrano-Munoz, I.; Buffiere, J.-Y.; Verdu, C.
Abstract: The influence of defects parameters ( i.e., size, shape and location) on early crack nucleation in an A357-T6 cast aluminium alloy is studied by means of synchrotron in situ fatigue testing and 3D microstructure based FE simulations. An experimental procedure using laboratory tomography is developed to produce specimens containing controlled internal defects. Two types of defects are investigated: natural shrinkages and artificial defects. Results show that is not possible to assert the harmfulness of a defect if only its size (using A parameter) is taken into account. Location is critical: it is observed that ten times smaller surface defects are able to lead to final failure even when a ∅  = 1 mm internal artificial defect is present within the specimen gauge. Regardless the size, location and nature (artificial or shrinkages) of the defect, the shape is also a factor to take into account because the earliest crack nucleation are observed to occur at regions were the K t values are the highest. For defects of similar nature and size, K t evaluations give good indication of the defect tendency to early nucleation.